Comparative Study of Deep-Bedded Pack Compost Relative to Organic and Inorganic Amendments for Enhancing Growth and Productivity of Aman Rice in Bangladesh - Dhakal, Hem Raj; Kabir, A.K.M. Ahsan; Gulshan, Zubaida; Rahman, Mohammad Mukhlesur; Amin, Ruhul; Khan, Rokibul Islam (Journal of Agriculture and Forestry University, 2026)
The deep bedded pack (DBP) system is a modern loose housing method for dairy cows that enhances comfort by providing an open-bedded area for resting and exercise. In DBP, dung and urine are mixed with bedding materials, which is cultivated 1–3 times daily. DBP compost, derived from this system, serves as an organic manure. This study evaluated the effect of DBP compost on Aman rice production. A study was initiated in Satkhira, Bangladesh, from 1st June 2020 to 31st July 2021 with five treatments as T1: Control (no fertilizer), T2: Chemical fertilizer (CF) as Recommended Dose (RD), T3: Biochar + RD, T4: DBP Compost + RD, and T5: DBP Compost + Biochar + RD. The DBP compost had 66.47% moisture, pH 8.30, organic carbon 21.89%, total nitrogen 1.83%, C:N 13.68, phosphorus 0.29%, potassium 1.57%, and sulfur 0.3%. Most yield parameters differed significantly (p